2009
DOI: 10.1038/tpj.2009.40
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of stem cells derived from human third molar tooth germs of young adults: implications in neo-vascularization, osteo-, adipo- and neurogenesis

Abstract: A number of studies have reported in the last decade that human tooth germs contain multipotent cells that give rise to dental and peri-odontal structures. The dental pulp, third molars in particular, have been shown to be a significant stem cell source. In this study, we isolated and characterized human tooth germ stem cells (hTGSCs) from third molars and assessed the expression of developmentally important transcription factors, such as oct4, sox2, klf4, nanog and c-myc, to determine their pluri-potency. Flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
106
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(117 citation statements)
references
References 44 publications
7
106
0
4
Order By: Relevance
“…As reported in previous studies on human stem cells (Ulloa-Montoya et al 2007;Yalvac et al 2010), Oct-4, Nanog and Sox-2 showed different relative gene expression in the cell line isolated and this is probably due to different regulatory mechanisms of these genes (Barrand and Collas 2010). Amnion cells did not express CD34, a known cell marker expressed by hematopoietic stem cells.…”
Section: Discussionmentioning
confidence: 51%
“…As reported in previous studies on human stem cells (Ulloa-Montoya et al 2007;Yalvac et al 2010), Oct-4, Nanog and Sox-2 showed different relative gene expression in the cell line isolated and this is probably due to different regulatory mechanisms of these genes (Barrand and Collas 2010). Amnion cells did not express CD34, a known cell marker expressed by hematopoietic stem cells.…”
Section: Discussionmentioning
confidence: 51%
“…4 MSCs are found in bone marrow, muscle, liver, placenta, peripheral blood, synovial fluid, dental pulp, and adipose tissue. 5 They have been shown to differentiate into bone, cartilage, adipose, muscle, and nerve cells when stimulated with appropriate biological and chemical signals.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that extracted impacted third molars are capable of producing an optimum quantity of dental pulp tissue for the isolation of DPSCs [9,10]. Various methods have been described for isolation of stem cells from human dental pulp.…”
Section: Discussionmentioning
confidence: 99%